British Parliamentary Debate System: Students’ Perspective on Their Learning Outcome - Wahyuni, Sri; Qamariah, Hijjatul; Gani, Sofyan A.; Yusuf, Yunisrina Qismullah; Syahputra, Mulyadi (International Journal for Educational and Vocational Studies, 2019)
This study was conducted to investigate the students’ perceptions on the classroom debate’s learning outcome using British Parliamentary debate system. Fifteen students were randomly selected and assigned to a group and actively involved in the debate in ten sessions during a whole semester. The obtained data of this study were collected through a survey questionnaire using 5-point Likert scale and interviews five random five participants to validate the data of the questionnaire and further analyze using mix method that combines between qualitative and quantitative approaches. The result of the data showed that the students indicated a positive perspective on its learning outcomes through the implementation of British Parliamentary Debate System in term of students’ interest, subject matter, communication skill, critical and creative thinking, intrapersonal and interpersonal development skill.